Understanding the lived experience of Malaysian Indian prison detainees of their gang life - Suppiah, Veera Sundari (2021)
Gangsterism and gangs are pervasive and include every ethnicity in Malaysia, but the participation of Malaysian Indians has reached an alarmingly high level. The involvement of Malaysian Indian in gangsterism has very high impact on society and the peace and harmony of the society and nation. Consequently, the emphasis of this research was on Malaysian Indian prison detainees who were involved in gangs. Transcendental Phenomenology approach of qualitative research design used to explore the lived experiences of twelve Malaysian Indian prison detainees who were detained for their involvement with gang violent activities. This is to gain an in-depth understanding of the lived experiences of the gangsters about the journey of their gang life. Data collection included semi structured interviews. The study utilized purposeful and homogenous sampling strategies. It was guided by three research questions: 1) What did the detainees understand about gangs and gangsterism? 2) Why did the detainees join the gangs? 3) What is the detainees’ life experience as a gang member or gangster? Analysis of the data from the first research question understanding about gangs and gangsterism provided two themes namely togetherness and violence. The findings showed that the detainees have knowledge about the organizations and its activities before they join gang. There were two themes emerged from the analysis based on the second question. Marginalization with four subthemes as poverty, environment, leadership and protection. The second theme was physical attraction and culture. These themes, which create the phenomenon that describes the lived experiences of the detainees, formed the basis of the findings of the study. The findings indicated that, marginalization followed by prejudice and inequality, was the underlying reason of Malaysian Indian engagement in gangsterism. As a marginalized population, Malaysian Indians face significant familial, economic, peer pressure, neighbourhood, and education issues. Some commit crime based on their own choice nevertheless they are aware of the seriousness and the impact of being a gang member. The older detainees joined gang mainly for family and people around them and the younger detainees were to gain their satisfaction. Based on the experience shared, new fact emerged unexpectedly which is the talent of informant that was not noticed and encouraged. Based on the shared experience, an unexpected new fact emerged which was the talent of informers that was not realized and encouraged. This shows that gangsters are not born to be but created by the atmosphere and irresponsible parties. As a whole, the findings also demonstrated that the reality of gang life differs from the expectations of the informants. The informants endured a great deal of suffering throughout their lifetimes. The majority of informants have recognized their mistakes and desire to leave the gang, but the circumstance is very challenging. These findings of the study mainly support social Learning Theory and social Conflict Theory. In terms of practical implications, this study would help the parents, teachers and society to understand about gangsters and create a better life for them and help to maintain a peaceful and harmonious country.